Beyond structural listening? : postmodern modes of hearing - Dell'Antonio, Andrew (University of California Press, 2004)
Rose Subotnik criticized 'structural listening' as an attempt to situate musical meaning solely within the unfolding of the musical structure itself. The authors of this volume take up her challenge, writing on repertoires ranging from Beethoven to MTV.